2018
DOI: 10.3390/su10124791
|View full text |Cite
|
Sign up to set email alerts
|

Engaging the Private Homeowner: Linking Climate Change and Green Stormwater Infrastructure

Abstract: Current and projected climate change in the Minnesota Lake Superior Coastal Area indicates an increase in frequency and intensity of extreme rainfall. One key outcome of this change is a subsequent potential increase in stormwater runoff, a concern exacerbated by the region’s shallow, often clay soils and exposed bedrock, along with highly impervious urban surfaces. This situation, coupled with public perception of climate change that is increasingly inclusive of severe weather, highlights an opportunity to ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 25 publications
1
18
1
Order By: Relevance
“…This concern includes impacts of stormwater run-off on recreation infrastructure, for example, severe erosion on Duluth trails and in parks. Stormwater management is a challenge in Duluth based on the local topography (steep hillsides down to Lake Superior), clay soils, exposed bedrock, and urbanization [49]. In addition, the loss of Black Ash will harm regional cultural traditions [47].…”
Section: Complexity Of Climate Trends and Impacts On Outdoor Recreationmentioning
confidence: 99%
See 1 more Smart Citation
“…This concern includes impacts of stormwater run-off on recreation infrastructure, for example, severe erosion on Duluth trails and in parks. Stormwater management is a challenge in Duluth based on the local topography (steep hillsides down to Lake Superior), clay soils, exposed bedrock, and urbanization [49]. In addition, the loss of Black Ash will harm regional cultural traditions [47].…”
Section: Complexity Of Climate Trends and Impacts On Outdoor Recreationmentioning
confidence: 99%
“…Another example of this growing climate concern was the growth of the Twin Ports Climate Conversations (TPCC), a Duluth area monthly presentation and discussion on a wide variety of climate change-oriented topics [69]. Given the growing importance of outdoor recreation to the area economy [70] in sync with the growth in climate change awareness [49], a specific focus on climate resilience relative to outdoor recreational resources was deemed as an important focus by Sea Grant Extension Educators in collaboration with numerous actors in the community, not least University of Minnesota professionals, Minnesota state climatology professionals, and outdoor recreation leaders. It was hoped that climate resilience emphasizing outdoor recreation could serve as a positive, unifying direction for the community [71].…”
Section: Identifying the Problemmentioning
confidence: 99%
“…In addition, Byrne et al [35] took tree plant activities in public space as a case study, developed a model combining residents' social variables (e.g., gender, age, and education level) and tree benefit perception, and found that older people with higher tree benefit perception are more willing to plant trees in public space to promote climate adaptation change in Hangzhou, China. Beery et al [36] suggested that improving residents' cognition of GI and perception of pluvial flood risk play an important role in promoting residents' active participation in the implementation of GI. In general, many studies suggested that public involvement is needed, and the barriers to implementation are policy, technology, perception, funding, residents' living experiences, etc.…”
Section: Introductionmentioning
confidence: 99%
“…As another method of increasing infrastructure resilience, risk assessment has been commonly used in the studies conducted by Ruijters and Stoelinga (2016); Hall et al (2016); Do and Jung (2018); Mao et al (2018); Wang et al (2019); and Tsavdaroglou et al (2018). The selected studies also highlight that within the water sector, combining green and grey infrastructures (nature-based solutions) is the most frequently used approach to increase system's resilience (e.g., Hulscher et al, 2014;Augustijn et al, 2014;Demuzere et al, 2014;Borsje et al, 2017;Augustijn et al, 2018;Beery, 2018;Vuik et al, 2019).…”
Section: Recent Applications In Literaturementioning
confidence: 99%